A Study of Global Health Elective Outcomes: A Pediatric Residency Experience. (9th January 2017) - Russ, Christiana M.; Tran, Tony; Silverman, Melanie; Palfrey, Judith
Background and Objectives: To identify the effects of global health electives over a decade in a pediatric residency program.Methods: This was an anonymous email survey of the Boston Combined Residency alumni funded for global health electives from 2002 to 2011. A test for trend in binomial proportions and logistic regression were used to document associations between elective and participant characteristics and the effects of the electives. Qualitative data were also analyzed.Results: Of the 104 alumni with available email addresses, 69 (66%) responded, describing 94 electives. Elective products included 27 curricula developed, 11 conference presentations, and 7 academic publications. Thirty-two (46%) alumni continued global health work. Previous experience, previous travel to the site, number of global electives, and cumulative global elective time were associated with postresidency work in global health or with the underserved.Conclusions: Resident global electives resulted in significant scholarship and teaching and contributed to long-term career trajectories.